RING MATRIKS ATAS RING KOMUTATIF - Achmad Abdurrazzaq; Ari Wardayani; Suroto Suroto (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2015)
This paper discusses a matrices over a commutative ring. A matrices over commutative rings is a matrices whose entries are the elements of the commutative ring. We investigates the structure of the set of the matrices over the commutative ring. We obtain that the set of the matrices over the commutative ring equipped with an addition and a multiplication operation of matrices is a ring with a unit element.